Effects of Flour Shell Mussels (Perna Viridis sp.) to The Serum Levels of Calcium in Male Local Rooster - Era Hari Mudji; Muhammad Zaki Mubarah (VITEK : Bidang Kedokteran Hewan, 2015)
This study aimed to determine the effects of adding flour shell mussels (Perna viridis sp) On serum levels of calcium in the male range chicken. This study uses a completely randomized design (CRD) with 4 treatments, and each treatment be repeated 5 times. Treatment consists of : Giving green shells flour 0%, 0.9%, 1.8%, 2.7%. Data were analyzed by Duncan's test and LSD.The results showed that administration of green flour shells with multiple levels in the male range chicken was highly significant (P <0.01) on serum calcium levels range chicken males, Conclusions of this study are : Provision of additional flour shell mussels feed on male domestic poultry as a source of minerals with a dose of 0%, 0.9%, 1.8%, 2.7% had an influence on serum calcium levels in the blood.